The use of dietary supplements among soccer referees: How much do they know? - Malaguti, M.; Scarpino, M.; Angeloni, C.; Hrelia, S. (Journal of Human Sport & Exercise, 2019)
Referees are essential for the correct execution of each soccer match and national soccer associations support them with physical training guidelines in order to improve agility, aerobic and sprint capacity, to reduce the risk of injury and to meet the minimum required performance levels. Despite the importance given to performance skills no specific nutritional guideline is provided to support the performance required. This study was aimed to investigate soccer field and assistant referees knowledge and consumption of dietary supplements. Seventy-one European referees participated to this survey by filling a short and quick anonymous questionnaire designed to collect information about their refereeing category, educational level, frequency of supplement consumption, type of supplement consumed. Moreover, a sub-group of 20 participants wore a training watch to record energy expenditure, distance, and heart rate during training sessions and matches. Our data show that referees frequently consume supplements especially those refereeing in lower categories, moreover they often follow a friend`s suggestion when deciding to take a supplement instead of trusting a professional prescription. According to our survey, national and international soccer federations should care more about their referee nutritional education.